Parathyroid adenoma with rare severe pathological osteolytic lesion: a case report and literature review - Chen, Jia; Tang, Gusheng; Peng, Ye; Cheng, Hui (Frontiers in Oncology, 2023)
Parathyroid adenomas are benign proliferative disorders of parathyroid glands. Patients typically exhibit hyperparathyroidism and elevated serum calcium levels due to elevated levels of parathyroid hormone (PTH). We report a newly diagnosed case of a rare pathological osteolytic lesion. Radiological evaluation revealed multiple bony lesions in multiple parts of the pelvis, vertebral body, and spinous process, suggesting hematological neoplasms or bone marrow metastatic carcinoma. The morphology revealed many abnormal cells in the bone marrow smear. Furthermore, serum calcium and PTH levels were significantly increased compared to normal levels. Doppler color ultrasound showed a thyroid mass (left), suspected parathyroid adenoma, thyroid, and isthmus nodular goiter (right). The patient underwent bilateral neck exploration with parathyroidectomy, and serum calcium and PTH levels significantly decreased on the second day after surgery and had a surgical cure.